Análise sedimentológica e biodetrítica da plataforma continental da porção centro-norte da bacia do Espírito Santo - Catunda, Bruno Nogueira (2019)
The Espírito Santo basin has a very heterogeneous morphology when compared to the other areas of the brazilian coast. The basin is located on the portion of the continental margin that corresponds to a physiographic domain of transition between the continental part and the ocean basin. This project will make it possible to characterize the substrate of the Espírito Santo Basin (Central-north Portion) by collected sediments in a timely manner (AMBES Project). The sedimentological and biodetritic characterization of this portion will consist of the analysis of sediments related to their granulometric characteristics, their calcium carbonate contents and also their organic matter. The biodetritic analysis will be divided by the material analyzed in the granule range to very coarse sand (Fraction 1) and medium to fine sand (Fraction 2). Samples were taken during winter and summer seasons. Collections of the two periods have showed a higher concentration of fine sand in total but the mud fraction has prevailed at some spots near Doce River mouth. Concentrations of organic matter during the winter were low with variations between 0.65% and 17.8% presenting higher levels closer to Piraquê-açu River mouth. Concentrations of organic matter during the summer were slightly higher with variations between 1.10% and 22.85% the highest concentrations were observed in the northernmost part of the Doce River. Levels of CaCO3 during the winter oscillated between 1.07% and 94.64%, while during the summer these values oscillated between 0.97% and 96,98%. The both seasons have had dominance of lithoclastic material near Doce River mouth and also at shallower depths. The shelf presents an increasing tendency in CaCO3 concentrations as the depth rises. In winter, the most abundant biodetritus in fraction 1 belonged to Phyla Bryozoa and Mollusca, classes Bivalvia and Gastropod, 45%, 33% and 9% were registered respectively. In fraction 2, the most abundant ones belonged to Phyla Foraminifera, Bryozoa and Mollusca, classes Bivalvia, containing of total abundance 42%, 25% and 12%, respectively. For samples collected in summer, the most abundant biodetritus in fraction 1 belonged to Phyla Bryozoa and Mollusca, classes Bivalvia and Rhyzopoda – 40%, 32% and 11 %, respectively. In fraction 2, the most abundant ones belonged to Phyla Foraminifera, Echinodermata and Porifera – 52%, 10% e 10% of total abundance, respectively. The Espírito Santo central-north portion continental shelf area is predominantly composed of sand. However, there is mud in some isolated spots, above all near Doce River mouth. Sediments have had high levels of organic matter in close proximity to rivers' mouths. In fraction 1, there is dominance of phyla Bryozoa and Mollusca, class Bivalvia – this last one with high incidence between 0 and 25 meters deep. In fraction 2, there is dominance of the phylum Foraminifera along the area studied. Nonetheless, there is dominance of the phylum Mollusca, class Bivalvia, near Doce River mouth, this last one with high incidence until 25 meters deep.